ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN DALAM PADA MENINGKATKAN KONSEP PADA MATA PELAJARAN IPA SRIWEDARI 02 - Tamman Firdaus Muqarrobin; Satri Wahyuni (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to analyze the need for learning media used to improve students' conceptual understanding of Natural Sciences (IPA) subjects at SDN Sriwedari 02. The background of this study is based on the importance of learning media as a tool in the teaching and learning process. The research method used is a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation. The research subjects include science teachers and students. The results of the study indicate that the learning media that have been used so far are quite good and able to help students understand science materials. However, the needs analysis shows that there is still room for the development of more varied and contextual media, to support more effective learning.